Analisis Kelayakan Usaha Tani Cabai Merah Besar (Capsicum annuum L.) di Kabupaten Karanganyar, Jawa Tengah - Suryadi, Didik; Suprihatin, Dewi Nawang; P, Anditya Gilang Rizky; Suhita, Cahyaningtyas Putri; Setyaningrum, Desy; Hantari, Dimar; Paryanto, Edi; Nurhidayati, Febry; Arifin, Zainal; Ningsih, Hardian (Jurnal Kridatama Sains dan Teknologi, 2025)
Chili has high economic value and is one of the commodities that determine inflation in Indonesia. Chili farming faces various challenges, such as dependence on production inputs and high climate risks. This study aims to analyze the cost structure, revenue, and profit of the chili farming, as well as evaluate the feasibility of chili farming in Karanganyar Regency. The study used 100 primary data obtained through structured interviews with chili farmers using questionnaires. Farming business analysis was conducted to explain the cost structure, income and profits of large red chili farming businesses. The feasibility of chili farming is analyzed using profit, R/C ratio, ROI, and BEP as indicators. The results of the analysis show that chili farming in Karanganyar Regency requires costs of Rp 50,838,529/ha for one planting season. The largest proportion of costs is labor expenses, which reach Rp 16,735,396/ha, or 32.92% of the total costs. With a productivity of 5,132 kg/ha, the chili farming can provide an income of Rp 161,782,703/ha and generate profits of Rp 111,083,320/ha. When converted based on the actual land area and planting period, the profit from chili farming is Rp 5,571,921/month; this value is higher than the regency minimum wedge value (UMK) of Karanganyar Regency. The business feasibility evaluation shows an R/C ratio of 3.19, an ROI of 219%, a BEP unit of 1,613 kg, and a BEP price of Rp 9,907/kg. These findings indicate that chili farming in Karanganyar Regency is feasible to run